Intensive intervention and risk management services (IIRMS) three years on: what we need to do better in the offender personality disorder pathway. Issue 4 (17th November 2021) - Craissati, Jackie; Ramsden, Jo; Ryan, Sue; Webster, Nicole; West, Laura
Abstract : Purpose: This is a discussion paper describing the reflections of clinical leads within well-established intensive intervention and risk management services (IIRMS). IIRMS has developed in the past five years, with a small number of services leading in the development of a psychologically informed case management approach to working with individuals released from prison on probation licence, who have a history of high risk, high harm violent convictions linked to pervasive psychological and interpersonal problems. Design/methodology/approach: Clinical leads of three services considered a period of 23 months up to December 2019, in which the outcomes for all individuals on their caseload at that time were reviewed. Reflections on the themes included the reasons for a premature return to prison and emerging themes for those who appeared to be successfully resettled. Findings: Approximately one-third of the individuals were returned to prison, and for most, this occurred within the first 18 months of release. There was considerable unanimity between clinical leads regarding the themes, and problems with relative youth, substance misuse, relationship difficulties, managing transitions and complacency featured. There were four themes identified in those who appeared to have settled successfully in the community. Practical implications: The identified themes provide key learning that will be enshrined in an updated version of the guidance for all IIRMS, with the overall aim of reaching out and engaging with a group of individuals who are most at risk of exclusion from services. Originality/value: Although there are limitations associated with the informal approach of this paper, the reflections of the clinical leads have provided a valuable addition to the very limited empirical literature in this field.